Completing Single-Cell DNA Methylome Profiles via Transfer Learning Together With KL-Divergence - Dodlapati, Sanjeeva; Jiang, Zongliang; Sun, Jiangwen (Frontiers in Genetics, 2022)
The high level of sparsity in methylome profiles obtained using whole genome bisulfite sequencing in the case of low biological material amount limits its value in the study of systems in which large samples are difficult to assemble, such as mammalian preimplantation embryonic development. The recently developed computational methods for addressing the sparsity by imputing missing have their limits when the required minimum data coverage or profiles of the same tissue in other modalities are not available. In this paper, we explored the use of transfer learning together with Kullback-Leibler (KL) divergence to train predictive models for completing methylome profiles with very low coverage (below 2%). Transfer learning was used to leverage less sparse profiles that are typically available for different tissues for the same species; while KL divergence was employed to maximize the usage of information carried in the input data. A deep neural network was adopted to extract both DNA sequence and local methylation patterns for imputation. Our study of training models for completing methylome profiles of bovine oocytes and early embryos demonstrates the effectiveness of transfer learning and KL divergence, with individual increase of 29.98% and 29.43%, respectively, in prediction performance and 38.70% increase when the two were used together. The drastically increased data coverage (43.80%-73.6%) after imputation powers downstream analyses related to methylomes that cannot be effectively done using the very low coverage profiles (0.06%-1.47%) before imputation.